Challenges and Choices for Crime-Fighting Technology Federal Support of State and Local Law Enforcement - Schwabe, William (RAND Corporation, 2001)
Under the American federal system, most law is cast as state statutes and local ordinances; accordingly, most law enforcement is the responsibility of state and local agencies. Federal law and federal law enforcement come into play only where there is rationale for it, consistent with the Constitution. Within this framework, a clear role has been identified for federal support of state and local agencies. This report provides findings of a study of technology in use or needed by law enforcement agencies at the state and local level, for the purpose of informing federal policymakers as they consider technology-related support for these agencies. In addition, it seeks to characterize the obstacles that exist to technology adoption by law enforcement agencies and to characterize the perceived effects of federal assistance programs intended to facilitate the process. The study findings are based on a nationwide Law Enforcement Technology Survey and a similar Forensics Technology Survey (FTS) conducted in late spring and early summer2000, interviews conducted throughout the year, focus groups conducted in autumn 2000, and review of an extensive, largely nonacademic literature. Companion reports: Schwabe, William, Needs and Prospects for Crime-Fighting Technology: The Federal Role in Assisting State and Local Law Enforcement, Santa Monica, Calif.: RAND, 1999. Davis, Lois M., William Schwabe, and Ronald Fricker, Challenges and Choices for Crime-Fighting Technology: Results from Two Nationwide Surveys, Santa Monica, Calif.: RAND, 2001.